The competence of nurse educators and graduating nurse students - Salminen Leena; Tuukkanen Minna; Clever Katharina; Fuster Pilar; Kelly Mary; Kielé Viktorija; Koskinen Sanna; Sveinsdóttir Herdis; Löyttyniemi Eliisa; Leino-Kilpi Helena; PROCOMPNurse-Consortium (Elsevier, 2022)
Background: A nurse educator has an important role in promoting students' learning and professional development as well as in offering high quality nursing education.
Objectives: To describe the competence of nurse educators and explore its connection with the self-evaluated competence of graduating nurse students.
Design: A cross-sectional survey design was used.
Participants: A total of 1796 graduating nurse students in Finland, Germany, Iceland, Ireland, Lithuania and Spain participated in this study.
Methods: The data were collected with structured electronic or paper-and-pencil questionnaires. Graduating nurse students evaluated the nurse educators' competence using six items derived from the Tool for Evaluation of Requirements of Nurse Teacher (ERNT) and in addition, the students evaluated their own generic professional competence using the Nursing Competence Scale (NCS). The data were analysed statistically.
Results: On average, graduating nurse students evaluated the competence of nurse educators to be rather high. Icelandic and Irish students evaluated nurse educators' competence the highest. German and Finnish students were the most critical. The students also evaluated the level of their own professional competence as good. The higher graduating nurse students evaluated their own competence, the higher they also evaluated their nurse educators' competence.
Conclusions: Students' evaluations of their educators' competence and their own competence seem to be aligned. However, educators' competence and its connection with students' competence warrants further studies.